Pemberian sanksi bagi notaris yang melakukan publikasi atau promosi diri di media cetak maupun media elektronik - Fadhil Fahmi; Nurini Aprlianda; Dyah Aju Wisnuwardhani (Jurnal Cakrawala Hukum, 2020)
Notary is a general official who in carrying out his duty must follow the rules that exist in the form of law of the notary department and the profession Ethics notary. In writing this thesis the author raises the title of meaning of publication or promotion for the notary in the form of advertisements in print Media and electronic Media set in the notary code of conduct. In this research the author raises two cases of problems which consist of (1) whether the granting of sanctions in the notary code of ethics reflects the justice for the notary who conducts the publication or promotion in the print media or electronic media.In research to aim to provide explanation about the sanction of sanctions for notary public who conduct publication or self-promotion in print media and electronic Media which are reviewed from the principle of legal justice.From the results of this study refers to the granting of sanctions for notarized publications or self-promotion in printed media and electronic media that is reviewed from the legal justice principles contained in the notary Code of Ethics: which can not be said Fulfilling the legal justice element because the notary code itself is still considered too rigid for the development of the era and can not accommodate or follow the technological developments are very high and fast.How to cite item: Fahmi, F., Aprlianda, N., Wisnuwardhani, D. (2020). Pemberian sanksi bagi notaris yang melakukan publikasi atau promosi diri di media cetak maupun media elektronik. Jurnal Cakrawala Hukum, 11(2), 157-165. doi:https://doi.org/10.26905/idjch.v11i2.4450